Earthquake and Fire Disaster Evacuation Route Plan at Siliwangi University - Setio Galih Marlyono; Dede Wahyu Firdaus; Dita Agustian (Universitas Pendidikan Indonesia, 2024)
The natural state of West Java province, especially Tasikmalaya City, which is vulnerable to earthquakes and fires, requires humans to do disaster mitigation in order to minimize the risk and impact of disasters. This includes Siliwangi University which is located in an area with a fairly high potential to be affected by earthquakes and the possibility of a fire disaster that is quite vulnerable. Geographical characteristics and university buildings need to be considered in designing an effective evacuation route. The purpose of this research is to increase the University's readiness and response to earthquake and fire disasters, as well as ensure maximum safety for all academic and administrative communities at Siliwangi University. The approach in this study uses quantitative descriptive. The results showed that the highest availability of disaster facilities and infrastructure of Siliwangi University (Per Building) was 80.95% (University Clinic) and the lowest was 2.38% (FIK RKU Bawah); the highest availability of disaster facilities and infrastructure of Siliwangi University (Per Facilities) was 29.79% (Light Fire Extinguishing/APAR) and the lowest was 2.13% (Disaster Management Post). In conclusion, there needs to be an increase in disaster mitigation preparations at Siliwangi University, Tasikmalaya City.